Analisis Pengaruh Daya Saing Negara Kompetitor dan Determinan Lainnya Terhadap Volume Ekspor Kelapa Sawit Indonesia Ditengah Kebijakan Renewable Energy Directive - Salvacesa, Aftadhea; Ervani, Eva (Pustaka Peradaban, 2025)
As the world’s largest producer and exporter of crude palm oil (CPO), Indonesia has experienced a decline in exports to the European Union since 2016 due to the Renewable Energy Directive (RED) policy and Malaysia’s growing competitiveness. This study aims to analyze the influence of competitor countries’ competitiveness and other determinants on Indonesia’s palm oil export volume to five EU countries (the Netherlands, Germany, Spain, Italy, and Greece). The analysis uses panel data covering the period 2001–2023 with the fixed effect regression method. The findings show that the GDP of destination countries, population, Malaysia’s palm oil competitiveness and productivity, as well as the RED policy, significantly affect export volume. In contrast, the real exchange rate, world palm oil prices, world peanut oil prices, and Indonesia’s palm oil productivity have no significant effect. These results highlight the dominant role of external factors in influencing Indonesia’s CPO exports. The implication is that national strategies should focus on enhancing competitiveness, modernizing agriculture, and strengthening trade diplomacy that adapts to international environmental regulations to ensure long-term export sustainability. Sebagai produsen dan pengekspor CPO terbesar di dunia, Indonesia mengalami penurunan ekspor ke Uni Eropa sejak 2016 akibat kebijakan Renewable Energy Directive (RED) dan meningkatnya daya saing Malaysia. Penelitian ini bertujuan menganalisis pengaruh daya saing negara pesaing serta faktor determinan lain terhadap volume ekspor minyak kelapa sawit Indonesia ke lima negara Uni Eropa (Belanda, Jerman, Spanyol, Italia, dan Yunani). Analisis menggunakan data panel periode 2001–2023 dengan metode regresi fixed effect. Hasil penelitian menunjukkan bahwa PDB negara tujuan, populasi, daya saing dan produktivitas kelapa sawit Malaysia, serta kebijakan RED berpengaruh signifikan terhadap volume ekspor. Sebaliknya, nilai tukar riil, harga minyak kelapa sawit dunia, harga minyak kacang tanah dunia, dan produktivitas kelapa sawit Indonesia tidak berpengaruh signifikan. Temuan ini menegaskan dominasi faktor eksternal dalam memengaruhi ekspor CPO Indonesia. Implikasinya, strategi nasional perlu diarahkan pada peningkatan daya saing, modernisasi pertanian, dan diplomasi dagang yang adaptif terhadap regulasi lingkungan internasional untuk menjaga keberlanjutan ekspor jangka panjang.